2022
DOI: 10.32677/ijch.2017.v04.i02.010
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of foreign bodies in air passages

Abstract: Background: Foreign body in the airways is a serious event and fatal if not managed properly in time. Accident resulting from the inhalation of the foreign body continues to take formidable toll of lives every year.Objecti ve: This study was undertaken to find out the incidence of foreign bodies in air passages in this part of the country and types of foreign bodies, to establish the role of radiological investigations, and to find out the effective measures which are valuable in decreasing the post endoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…32% had emphysema followed by 28% collapse of lung whereas minimum 10% had consolidation whereas Nagaraj et al found that commonest radiological finding was obstructive collapse (37%). 10 In our study 30% of patients had normal chest X-ray finding whereas Wolach et al studied 127 children and found lesser (18%) chest X-rays were normal. 7 Higher proportion were found by Bai et al 52.4% had no abnormalities on plain X-ray and Meena et al In 95% X-rays was not confirmative.…”
Section: Discussioncontrasting
confidence: 47%
See 4 more Smart Citations
“…32% had emphysema followed by 28% collapse of lung whereas minimum 10% had consolidation whereas Nagaraj et al found that commonest radiological finding was obstructive collapse (37%). 10 In our study 30% of patients had normal chest X-ray finding whereas Wolach et al studied 127 children and found lesser (18%) chest X-rays were normal. 7 Higher proportion were found by Bai et al 52.4% had no abnormalities on plain X-ray and Meena et al In 95% X-rays was not confirmative.…”
Section: Discussioncontrasting
confidence: 47%
“…In our study majority 62% were male and 38% were female also Meena et al observed male preponderance whereas Nagaraj et al found 58 were males and 42 were females. 6,10 70% of study population was residing in rural area whereas 30% residing in urban area. Maximum 58% had lower socioeconomic followed by 40% middle and only 2% had upper socioeconomic status.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations